The Battle of Mataram Sultanate and VOC Against Trunajaya Troops in Kediri (1678) - Yuwono, Ardi Tri; Braake, Gijsbert ter (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2025)
Trunajaya was a descendant of the Madurese rulers who fought the Mataram Sultanate. This resistance was triggered by the actions of Amangkurat I, ruler of the Mataram Sultanate, who in 1659 ordered the massacre of the ulama who supported Prince Danupoyo in an attempt to overthrow his power. In response, Trunajaya launched resistance in Surabaya, which was then under the control of the Mataram Sultanate, but his efforts were unsuccessful. This failure was caused by the support of Amangkurat I from the VOC (Vereenigde Oostindische Compagnie), which forced Trunajaya and the rest of his troops to retreat to Kediri. While in Kediri, Trunajaya succeeded in building a new military force which became a threat to the Mataram Sultanate, so that the Mataram Sultanate together with the VOC tried to crush Trunajaya's resistance in Kediri. This research aims to explore further the military campaign carried out by the Mataram Sultanate and the VOC in crushing Trunajaya's resistance in Kediri. This research applies historical methods with a qualitative approach. Between 13 October and 15 November 1678, Mataram Sultanate troops and VOC troops had difficulty entering Kediri due to the strong current of the Brantas River. On November 25, 1678, they succeeded in entering Kediri City and attacked the Trunajaya fort. On the night of November 26, 1678, the Mataram Sultanate and VOC troops achieved victory, forcing Trunajaya and the rest of his troops to flee to Mount Panderman.